Erythrocyte membrane fluidity as a marker of diabetic retinopathy in type 1 diabetes mellitus. (1st December 2020) - Bianchetti, Giada; Viti, Luca; Scupola, Andrea; Di Leo, Mauro; Tartaglione, Linda; Flex, Andrea; De Spirito, Marco; Pitocco, Dario; Maulucci, Giuseppe
Abstract: Background: A high level of glycosylated haemoglobin (HbA1c), which is a nonenzymatic glycosylation product, is correlated with an increased risk of developing microangiopathic complications in Diabetes Mellitus (DM). Erythrocyte membrane fluidity could provide a complementary index to monitor the development of complications since it is influenced by several hyperglycaemia‐induced pathways and other independent risk factors. Materials and methods: 15 healthy controls and 33 patients with long‐duration (≥20 years) type 1 Diabetes Mellitus (T1DM) were recruited. Diabetic subjects were classified into two groups: T1DM, constituted by 14 nonretinopathic patients, and T1DM + RD, constituted by 19 patients in any stage of diabetic retinopathy. Red blood cells (RBC) were incubated with the fluorescent Laurdan probe and median values of Generalized Polarization (GP), representative of membrane fluidity, were compared between the two groups. Baseline characteristics among groups have been compared with Student's t test or ANOVA. Values of P  < .05 were considered statistically significant. Results: All the participants were comparable for age, Body Mass Index (BMI), creatinine and lipid profile. The duration of diabetes was similar for T1DM (34.4 ± 7.8 years) and T1DM + RD (32.8 ± 7.5 years) subjects as well as values of HbA1c: (55.6 ± 8.1) mmol/mol for T1DM and (61.2 ± 11.0) mmol/mol for T1DM + RD, respectively. Erythrocyte plasmatic membranes of RD patients were found to be more fluid (GP: 0.40 ± 0.04) than non‐RD patients (GP: 0.43 ± 0.03) with a statistically significant difference ( P  = .035). Conclusions: Altered erythrocyte membrane fluidity may therefore represent a marker of retinopathy in T1DM patients as a result of post‐translational modifications of multifactorial aetiology (nonenzymatic glycosylation of proteins, generation of reactive oxygen species, lipid peroxidation).